REGULATION OF HEALTH CRISIS RISK ASSESMENT (DISASTER HEALTH) RELATED TO PRE-HEALTH CRISIS (PRE-DISASTER) STAGE MITIGATION EFFORTS FROM A HUMAN RIGHTS PERSPECTIVE - R.A. Tuty Kuswardhani; Memory Fitri Sitorus; I Nyoman Suyatna (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Indonesia is a country with a high level of disaster vulnerability, which has direct implications for the emergence of health crises. One important instrument in pre-disaster mitigation is the health crisis risk assessment. This study aims to analyze the regulations for health crisis risk assessments in the pre-disaster phase and formulate an ideal regulatory framework that provides legal certainty and protects human rights, particularly the right to health. The research method used is normative juridical, with a statutory and conceptual approach. The results indicate a disharmony between Minister of Health Regulation No. 75 of 2019, which requires annual risk assessments, and Head of the National Disaster Management Agency (BNPB) Regulation No. 02 of 2012, which stipulates a five-year risk assessment validity period. This disharmony has resulted in legal uncertainty and weak implementation of risk assessments at the community health center (Puskesmas) level. From a human rights perspective, this situation has the potential to hinder the fulfillment of the rights to health and the right to life. This study recommends the need for regulatory harmonization and the establishment of a risk assessment period that is adaptive, integrated, and human rights-based.